Prevalence of dyslipidemia in patients with type 2 diabetes mellitus: a hospital based study in Kishanganj, India - Mandal, Manisha; Kumari, Rina; Mukherjee, Arati (International Journal of Research in Medical Sciences, 2017)
Background: A major risk factors for cardiovascular disease in type 2 diabetes mellitus (T2DM) is dyslipidemia characterized by high plasma triglyceride (TG), low HDL and increased LDL. Early detection of dyslipidemia in T2DM can help in the management and prevention of cardiovascular disease. The present study is based on the detection of anomalous lipid profile in T2DM patients. Methods: A total of 35 T2DM patients with fasting blood glucose (FBG) > 110 mg/dL, and 32 subjects with FBG (70-110 mg/dL) were considered as controls. Serum samples were assayed for determination of the levels of total Cholesterol (TC), HDL, LDL, TG, and VLDL. Variables were compared between T2DM subjects and controls, with statistical significance at p ≤0.05. Results: The prevalence of dyslipidemia was 12 (34.29%) and 9 (25.71%) with abnormal lipids levels of TC and TG respectively whereas 11 (31.43%), 12 (34.29), and 9 (25.71%) were found with lipoprotein abnormalities of HDL, LDL and VLDL respectively in T2DM subjects either singly or in combination. The serum parameters TC, TG, HDL, LDL, and VLDL were significantly correlated to FBG levels in both diabetic and non-diabetic subjects. The variables were also significantly associated among each other in T2DM patients. Conclusion: The present study provides evidence to suggest that lipid variables are associated with each other in T2DM patients among the population of Kishanganj, India.